2004
DOI: 10.1023/b:boun.0000037333.48760.e5
|View full text |Cite
|
Sign up to set email alerts
|

ONE- and TWO-Equation Models for Canopy Turbulence

Abstract: Abstract. The predictive skills of single-and two-equation (or K-e) models to compute profiles of mean velocity (U), turbulent kinetic energy (K), and Reynolds stresses ðu 0 w 0 Þ are compared against datasets collected in eight vegetation types and in a flume experiment. These datasets range in canopy height h from 0.12 to 23 m, and range in leaf area index (LAI) from 2 to 10 m 2 m À2 . We found that for all datasets and for both closure models, measured and modelled U, K, and u 0 w 0 agree well when the mixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
248
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(263 citation statements)
references
References 65 publications
10
248
1
4
Order By: Relevance
“…For reference, K-ε model results described in Katul et al (36) are also shown in Figure 1. Both the analytical and K-ε models captured the variations well in wind speed profiles measured by Wilson (39), with coefficient of determination (r 2 ) values of 0.987 and 0.989, respectively.…”
Section: Wind Profilesmentioning
confidence: 99%
“…For reference, K-ε model results described in Katul et al (36) are also shown in Figure 1. Both the analytical and K-ε models captured the variations well in wind speed profiles measured by Wilson (39), with coefficient of determination (r 2 ) values of 0.987 and 0.989, respectively.…”
Section: Wind Profilesmentioning
confidence: 99%
“…The problem is further complicated over forests since the forest applies a significant drag to the incoming flow, providing a spectral shortcut in the energy transfer between large and small scales of motion (Baldocchi and Hutchison 1988;Finnigan 2000). Svensson and Häggkvist (1990) and Katul et al (2004) suggested modifying the standard k − model equations for k and (namely the turbulent kinetic energy and the rate of turbulent kinetic energy dissipation, respectively) to account for such mechanisms. Silva Lopes et al (2013) provided expressions for the additional terms in the k − equations, validating them for several flow cases with different complexities.…”
Section: Introductionmentioning
confidence: 99%
“…Changes are manifest in a reduction in momentum in the model cell where the device is situated along with commensurate changes to turbulent kinetic energy and the turbulent kinetic energy dissipation rate. Sink terms, S Q , S K , and S ε , appropriate to each type of MHK device, represent the rate of momentum extraction, net change to turbulent kinetic energy, and the increase in turbulent kinetic energy dissipation rate, respectively [36]. In addition to the effects from the moving MHK device, the effects of affiliated support structures are also considered.…”
Section: Iiic2 Mhk Simulationmentioning
confidence: 99%
“…Over the last decade or so, various models have been proposed for S ε [36,42,43], but the simplest is used in this model:…”
mentioning
confidence: 99%